กรุปอินเวอร์สของเมทริกซ์ขนาด 3x3 เหนือริง - Wanicharpichat, Wiwat; Khambunlue, Natkodchanan (Naresuan University Journal: Science and Technology (NUJST); Vol 22 No 3 (2014): September-December 2014, 2014)
In this paper, we study conditions for the existence of the group inverse of the 3x 3 matrix   over an arbitrary ring R with unity 1, when   is the submatrix of N has the group inverse in R 2x2   Keywords: von Neumann regularity, {1,2} -inverse, Group inverse, Matrix over a ring.
Keywords: von Neumann regularity, {1,2} -inverse, Group inverse, Matrix over a ring